Optimizing Container Repositioning Using a Sequential Insertion Algorithm for Pickup-Delivery Routing in Export-Import Operations - Arvianto, Ary; Cahyani, Dihan Chofifah; Saputra, Dhimas Wachid Nur (Spektrum Industri, 2025)
The increasing number of empty containers significantly causes to traffic congestion and rising operational costs, thereby necessitating the development of an optimized routing model to enhance fleet utilization and minimize transportation expenses. This study focuses on optimizing container repositioning for pick-up and delivery operations using a heuristic approach derived from the Vehicle Routing Problem with Pick-Up and Delivery and Time Windows (VRPPD-TW). The proposed model employs a sequential insertion algorithm grounded in a mathematical framework and implemented in Python. Its accuracy is validated through manual calculations that correspond with the algorithmic steps. The objective is to minimize vehicle usage within the defined time constraints. This empirical study involves six nodes: a garage, two depots, two external container depots, and a port terminal, which handle the daily relocation of 44 containers for export-import activities. The model successfully reduces the number of trips from 37 to 6, demonstrating substantial optimization. The results show that the sequential insertion algorithm effectively solves the VRPPD-TW by enhancing solution space exploration, balancing workloads, and adapting to dynamic constraints. Managerial implications include a 75% reduction in fleet requirements and increased logistical efficiency. This research contributes a practical approach with the potential to lower operational costs and mitigate congestion by improving fleet utilization. However, the model has notable limitations, such as the exclusion of dynamic truck queuing times at each node and unresolved issues related to computational scalability.